The Impact of Selected Firm Features on Sales Growth: Empirical Evidence from S&P500 - (:unkn) unknown (SPRINGER INTERNATIONAL PUBLISHING AG, 2017)
Firm growth is an important research topic in the academic arena and accepted as a leading indicator of firm's health. However, the debate as to the determinants of growth has not yet been fully solved. Many studies concocted in developed and developing economies, already attempted to identify the driving forces that spur firm growth. This study investigates how selected factors influence sales growth of firms by employing 22 years of consecutive data on a sample of 243 nonfinancial Standard and Poor's 500 (S&P500) companies. The empirical findings of panel data analysis demonstrate significant influence of previous year sales growth, average growth rate of relevant industry, firm size, and change in profitability level on the selected proxy of firm growth. Additionally, financial leverage, market-to-book ratio, price-to-earnings ratio, and plowback ratio are not found to have any significant relationship with the growth rate of the firm. A crucial result to emphasize is that the market in which firms operate is the major force that spurs growth, and this impact is captured by the industry growth variable.
Keywords: CORPORATE-GROWTH; SIZE; RATES; AGE; INNOVATION; LIMITS